<<The>> spiritual consciousness of Carmen Martín Gaite - Storrs, Anne-Marie (Tamesis, 2023)
Spanish writer Carmen Martín Gaite (1925-2000) defined religioso as the reconnection of that which was previously united, namely, the day-to-day and supernatural worlds - here defined as consciousness and the unconscious, bringing awareness and wholeness. In this book, Martín Gaite's religious outlook is explored through the inner journeys of five female characters in El balneario, Lo raro es vivir, Irse de casa and Nubosidad variable.Spanish writer Carmen Martín Gaite (1925-2000) defined religioso as the reconnection of that which was previously united, namely, the day-to-day and supernatural worlds - here defined as consciousness and the unconscious, bringing awareness and wholeness. In this book, Martín Gaite's religious outlook is explored through the inner journeys of five female characters in El balneario, Lo raro es vivir, Irse de casa and Nubosidad variable.For Martín Gaite, a truly religious, or spiritual, perspective requires conscious attention to the products of the unconscious (dreams, images, memories, premonitions), followed by reflection and action, as well as a similar attentiveness and responsiveness to external events both large and small. This reconnection of the supernatural and day-to-day worlds also involves descent to the unconscious - the way to wholeness - as depicted in so many myths and fairy tales, including those which Martín Gaite used to retell or enhance the works analysed in this book: Sleeping Beauty, The Little Mermaid, Amor and Psyche, Demeter and Persephone, and the Descent of the Goddess Inanna.Looking at the extent to which these female characters attend to, reflect on, and respond to their dreams, images, memories and events, the analysis suggests that Martín Gaite uses her stories to try to communicate both the road to her own enlightenment and warnings about paths that lead away from this
9781855663886
Keywords: Spanische Literatur; Spanien; Hispanic Studies; Modern Literature; Portugal; Portugiesische Literatur; 20. Jahrhundert (1900 - 2000); Literarische Strömungen & Epochen; Gender Studies; Geschlechtersoziologie; Literaturgeschichte und Literaturkritik; Psychoanalyse (C.G. Jung); Literary studies: fiction; novelists & prose writers; Analytical & Jungian psychology; LITERARY CRITICISM / Modern / 20th Century; LITERARY CRITICISM / Women Authors; PSYCHOLOGY / Movements / Jungian; Religioso; El balneario; Lo raro es vivir; Irse de casa; Nubosidad variable; Sleeping Beauty; The Little Mermaid; Amor and Psyche; Demeter and Persephone; The Descent of the Goddess Inanna; Supernatural; Fairy Tales; Myths